Development Dashboard of Information STT Ibnu Sina Batam Method Using Object Oriented Analysis and Design (OOAD) - Dwi Putri Permatasari, Ririt; Ropianto, M.; Agung Prasetya, Wahyu; Herawan Hayadi, B.; Mouludi, Isra (International Journal of Engineering and Technology, 2018)
The increasing number of students encourages the management of STT Ibnu Sina Batam to continue to improve the service in terms of delivering important information in order to be implemented properly, effectively and efficiently. Almost all circles in universities both students and lecturers want to get information digitally. Some digital media have been created and used in various fields. Digital Dashboard is an information system that provides one-stop service that combines some important information needed by the academic community (Staff, Lecturer and Student). In designing the dashboard to make it easier to get all the information in STT Ibnu Sina Batam the author chose the method of Object Oriented Analysis and Design (OOAD) in order to produce the design of academic civitas academic information digital dashboard STT Ibnu Sina Batam modern.Â